Upaya Guru Membangun Karakter Disiplin Dalam Pembelajaran Online - Dwi Indah Yuniar (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to describe the teacher's efforts to build a disciplined character in online learning. In this study, qualitative research was used through a field study approach. It was conducted at MAN 2 Bogor City from January to May 2022. The primary data source was purposively selected teachers. The data collection technique is in-depth interviews, the data is validated by triangulation of sources. Data analysis using descriptive analysis by following the theory of Miles and Huberman. The results of this study indicate that the teacher's efforts to build disciplined character in online learning are carried out by: making learning contracts, through the camera through the Zoom Meeting application, and reminding students who are related to the tasks that must be done. Keywords: Teacher, Discipline, Daring Online